Extraction, purification and characterization of amylase enzyme from white pitaya (Hylocereus undatus (Haworth) britton & rose) peel using aqueous two- phase system - Shad, Zahra (2015)
Amylase is one of the most important enzymes largely used in biotechnological and industrial applications. Thirty percent of the World’s enzyme production is accounted by Amylase. Malaysia has around 927.4 ha (363.2 ha production areas) pitaya fruit-growing areas produces about 2,534.2 tons worth around US$3.5 million. Peels are one of the byproducts that are obtained from the processing of pitaya. Pitaya peel is mostly a waste material from fruit and beverage industries. Although it consists about 33% of whole fruit by weight and possesses valuable enzymes such as amylase, it is not being presently used commercially and is considered as a waste. It could have been efficiently used for commercial and economical production of natural enzymes. Therefore, this research studied the extraction, purification and characterization of amylase from white pitaya (Hylocereusundatus) peel. Extraction of amylase from peel of white pitaya was optimized using full factorial design (FFD) with three variables, sodium phosphate buffer (pH 4.5-7.5), mixing time (1- 3min) and buffer to sample ratio (1:3-1:5). The purification was carried out using aqueous two phase system (ATPS). The effectiveness of different parameters on purification and selective separation, such as polyethylene glycol (PEG) molecular weight (4000 to 8000), PEG concentration (10 to 18%), sodium citrate concentration (12-20%) and NaCl (2-8%) were optimized using response surface methodology (RSM). The purified amylase enzyme was characterized based on pH, temperature and metal ions, surfactants and oxidizing agents. It was found that optimum condition for amylase extraction was with sodium phosphate buffer pH 6 and buffer to sample ratio of (1:4) for 2 min which yielded the enzyme with specific activity of 5.89 U/mg. The purification of amylase was studied with ATPS method polyethylene glycol/sodium citrate. The optimum purification factor and yield were obtained when 14% (w/w) of polyethylene glycol 6000 g/mol, 16 % (w/w) sodium citrate buffer and 5% of NaCl were used. Amylase purification factor and yield using ATPS were 4.43 and 89.12%, respectively. The optimum temperature and pH activity of amylase were 55 °C and 6, respectively. This enzyme was also stable in the presence of surfactants and oxidizing agents. Moreover, it was found that the activity of amylase was increased in the presence of calcium ions. The unique characteristics of amylase from white pitaya peel indicate the great potential application of the enzyme in food and biotechnology industries.